The Prevalence of Microalbuminuria in Patients with Hypertension and Acute Ischemic Stroke - Abdur Rauf Hammad, Khurram Munir, Yamna Fatima, Sher Zamir, Qudsia Umaira Khan, Faizan Ahmed, (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: The purpose of this study was to ascertain the prevalence of microalbuminuria in hypertensive individuals who had recently suffered from an acute ischemic stroke. Study Design: Cross-sectional study Place and Duration: Department of Physiology, Sheikh Zayed Medical College, Rahim Yar Khan in the duration from July, 2022 to December, 2022. Methods: This study comprised 148 hypertension individuals of either sex who had suffered an ischemic stroke. Participants' full demographic information, including age, sex, BMI, and comorbidities, was recorded after obtaining informed written consent. Microalbuminuria was detected in a urine sample collected over the course of 24 hours using the Pyrogallol Red assay. Microalbuminuria was defined as a daily urinary albumin content of 30-300 mg. Association of Microalbuminuria was determined among all cases. SPSS 22.0 was used to analyze all data. Results: Among 148 cases, 87 (58.8%) were males and 61 (41.2%) were females. Patients mean age was 57.6±14.82 years and had mean BMI 25.9±7.48 kg/m2. Mean duration of HTN was 3.19±5.28 years. History of ischemic stroke was found in 14 (9.5%) cases, and family history of myocardial infarction found in 23 (15.5%) cases. Comorbidities were DM, CAD, Congestive heart failure, Atrial fibrillation and peripheral artery disease. We found Microalbuminuria in 68 (45.9%) cases. In 68 cases of microalbuminuria 38 cases had age >50 years, 19 cases were aged between 36-50 years and 11 cases were aged between 18-35 years. Conclusion: The high prevalence of microalbuminuria in hypertension patients with acute ischemic stroke led us to the conclusion that this marker can be used to reliably identify hypertensive individuals at high risk for ischemic stroke at a low cost. Keywords: Hypertension, Albuminuria, Ischemic stroke, Diabetes mellitus